Towards the individuated journalistic worker in pandemic times: Reflections from Greece and Cyprus - Vatikiotis, Pantelis; Maniou, Theodora A.; Spyridou, Lia Paschalia (My University, 2023)
Drawing on a comparative qualitative analysis using semi-structured interviews, this study examines the impact of the COVID-19 crisis on journalists’ working conditions and practices in Greece and Cyprus. The findings provide empirical evidence that the crisis had a significant impact on journalistic work: changing patterns in labour conditions, advancing the role of the individuated worker; cumulating levels of professional risks and stress; increasing insecurity and pressures in the sector – aspects that undermine journalism capacity to offer useful information needed for an informed and engaged citizenry. Still, these changes in both countries are not solely driven by the pandemic situation. Rather the recent crisis seems to have deepened structural pathogenies of journalism in both Greece and Cyprus, including sustainability issues intensified by the recent economic crisis, the lack of a strong professional culture that makes journalism vulnerable to political pressures, as well as dependences and deficiencies in interacting with new technologies.
Keywords: COVID-19 crisis; Cyprus; Greece; Journalism; Journalistic labour; Precarity